Bilateral Epidural Prefrontal Cortical Stimulation for Treatment-Resistant Depression - Nahas, Ziad (2010)
BACKGROUND: Treatment-resistant depression presents a serious challenge to both patients and clinicians. The anterior and midlateral prefrontal cortices play complementary roles in integrating emotional and cognitive experiences and in modulating subcortical regions. Both regions offer a distinct opportunity for targeted antidepressant treatments. We chose to pilot the safety and therapeutic benefits of chronic and intermittent epidural prefrontal cortical stimulation (EpCS) in patients with treatment-resistant depression. METHODS: We enrolled five adults with an average of 5.8 failed antidepressant treatments in their current depressive episode. All subjects underwent comprehensive clinical assessments, detailed neuropsychological testing, and presurgical magnetic resonance imaging. Four cortical stimulation paddle leads were stereotactically placed bilaterally over the anterior frontal poles and midlateral prefrontal cortex. We also acquired a postsurgical computed tomography scan and repeatedly assessed clinical outcomes over time of EpCS as an adjunctive treatment to constant medications. RESULTS: All patients tolerated the therapy. At 7-month follow-up, the average improvement from preimplant baseline on the Hamilton Rating Scale for Depression and the Inventory of Depressive Symptoms—Self-Report were 54.9% (± 37.7) and 60.1% (± 34.1), respectively. Three implanted subjects reached remission. One patient's left hemisphere leads were explanted 12 weeks postsurgery because of a scalp infection. CONCLUSIONS: Bilateral EpCS over anterior and midlateral frontal cortex is a promising new technology for treatment-resistant depression. Future double-blind studies are warranted.